Cover Picture: Chem. Eng. Technol. 4/2020. Issue 4 (24th March 2020) - Unknown
Abstract : Hydrogen: A Clean and Green Fuel of the Future. Copyright: Sonil Nanda Hydrogen is a clean energy vector and carrier. It shows not only a high heating value, but also releases water upon combustion. Moreover, hydrogen can be used as direct gaseous fuel in fuel cells or catalytically transformed into liquid hydrocarbon fuels such as green diesel and alcohols. Hydrogen is also used during the upgrading of alternative and synthetic hydrocarbon fuels by several hydrotreating technologies. Currently, most of the commercial hydrogen is produced from the catalytic reforming of natural gas and other fossil fuels, which results in significant levels of greenhouse gas emissions leading to global warming. However, hydrogen can be produced from waste biomasses, organic residues, and alternative resources through biological, thermochemical, hydrothermal, photoelectrochemical, electrochemical, photocatalytic, and other cleaner technologies. Over the long term, these sustainable processes for hydrogen production can have less environmental impacts and lead to a clean hydrogen‐powered energy sector.